A Platform for Development and Test of Spatio-Temporal Algorithms. - Seyed, Taraneh Baradaran (2011)
In-depth research of theoretical foundations of spatio-temporal databases and their indexing, leading to the development of software.
Keywords: dept.csc; faculty_collection; sabbatical_report

Meeting deadlines within object-oriented systems - El-Raouf, A.A. (International Conference on High Performance Computing and Simulation, 2011)
In real-time software systems, meeting deadlines is crucial. Software engineers face many challenges to model the object-oriented software system to handle complex real-time constraints. The accurate estimating of the performance time is a key criterion for a precise scheduling decision. This paper presents an object-oriented performance model that analyzes the behavior of the real-time objects' tasks whose executions are controlled by a scheduler. Each task is subject to a time/utility function (TUF) that determines the accrued utility of the task according to its completion time. The scheduling scheme uses both the estimated time generated by the object-oriented performance model and the time utility function (TUF) of each task in the object-oriented system in order to maximize the total accrued utility. In addition, we implemented a software tool to conduct experimental study in order to show the effectiveness of our approach. © 2011 IEEE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Proc. Int. Conf. High Perform. Comput. Simul., HPCS
Keywords: Completion time; Computer software selection and evaluation; Experimental studies; Object oriented; Object oriented software; Object-oriented software systems; Object-oriented system; Performance Model; Performance analysis; Real time constraints; Real time systems; Real-time software; Scheduling; Scheduling decisions; Scheduling schemes; Software engineers; Software tool; Time-utility functions; deadline; dept.csc; object-oriented software; performance analysis; scheduling; time utility function